The impact of GeoGebra AR on students' geometric thinking based on Van Hiele theory - Ruslau, Maria Fransina Veronica; Oswaldus Dadi; Nurlianti (Universitas Papua, 2025)
Traditional instructional approaches to teaching three-dimensional (3D) geometric shapes are often ineffective in promoting student engagement and deep conceptual understanding of geometric principles. This study investigates the integration of GeoGebra Augmented Reality (AR) as an innovative pedagogical tool for the enhancement of 3D geometry instruction and assesses its effectiveness in developing students' geometric thinking, based on Van Hiele’s theoretical framework. A series of interactive learning lessons facilitated students interactive with 3D models and dynamic simulations, aimed at fostering more robust conceptual understanding. The research employed a one-group pretest-posttest design involving 60 secondary school students who participated in geometry learning using GeoGebra AR. Data were collected through a geometric thinking test and categorized according to Van Hiele’s level taxonomy. Statistical analysis using the Wilcoxon signed-rank test revealed a significant improvement in students' geometric thinking levels following the intervention (p < 0.05), leading to the rejection of the null hypothesis. These findings provide empirical support for the effectiveness of GeoGebra AR in advancing students’ Van Hiele levels and enhancing their comprehension of geometric concepts. These results highlight the potential of GeoGebra AR as a pedagogically valuable tool for supporting students’ cognitive development in geometry and increasing their engagement in mathematics learning. Further investigations are recommended to examine the long-term impacts of GeoGebra AR across diverse educational contexts and demographic settings.